THE BUKHARA EMIRATE: A HISTORICAL OVERVIEW - Umar Kuziyevich Ergashev (Web of Journals Publishing, 2024)
The Bukhara Emirate, a significant political and cultural entity in Central Asia, existed from the 18th century until its dissolution under Soviet control in the early 20th century. Centered around the ancient city of Bukhara, the emirate was an important hub for trade, culture, and Islamic scholarship. It emerged following the decline of the Timurid Empire, with the Shaybanid dynasty consolidating power in the region. The political system was characterized by a combination of Islamic monarchy and religious governance, with the emir wielding both political and religious authority. The economy was driven by agriculture and trade, particularly along the Silk Road, while the region became a prominent center for intellectual and cultural activities. The eventual decline of the Bukhara Emirate was influenced by internal strife and external pressures, notably from the Russian Empire. The region ultimately fell under Soviet control in 1920, marking the end of the emirate as an independent entity. Despite its collapse, the legacy of the Bukhara Emirate continues to shape the cultural and political landscape of Central Asia.
Keywords: Bukhara Emirate, Central Asia, Islamic monarchy, Shaybanid dynasty, Silk Road, Islamic scholarship, trade, Russian Empire, Soviet Union, cultural legacy, Bukhara, Central Asian history, political decline.